Nas ruas e para além delas : um olhar comunicacional sobre a 1ª Marcha das Mulheres Negras e a 1ª Marcha das Mulheres Indígenas - Cecília Bizerra Sousa (2024)
This project sought to understand the organizational process of the First Black Women’s March (2015) and the First Indigenous Women’s March (2019) through the analysis of communicative interactions established throughout the construction process of these two mobilizations. Through the lenses offered by the black feminist theories and the Praxiological Model of Communication, and also with a corpus composed of 10 interviews (five leaders from each march), it is examined the interactional dynamics, observing their outcomes, and identifying shared elements and how they influence the construction of the individual subjects, the marches, the movements to which they are connected, and also, the unfolding of communicative processes. It was observed that, through a process of consciousness-raising, these women started developing strategies to confront mechanisms of oppression not only through the adoption of methods of individual resistance but also through involvement in collective initiatives, such as the marches under analysis. This is what I refer to, in this thesis, as a rupture with the social place of imposition to occupy the social place of emancipation. From this new social place of emancipation, different types of social and political actions led by racialized women are created and implemented, among which I distinguish two main ones: a) organized political action, and b) strategies and actions in other areas that compose and create the foundations of an organized political action. A new social place is erected, and within there (and from there), the marching women develop strategies for the transformation of their lives and their surroundings through their social practices. It is not only the marches that create this new place, but they are essential in consolidating the position that are shaping them. While evoking ancestral elements, they reflect the vanguard as they print their own, innovative, and even transgressive forms of public appearance, which turn to indicate possibilities for changes in positioning, occupation of new places, and processes of consciousness-change that act as catalysts for social transformations. Finally, the social place of emancipation also produces pictures that go against the social place of imposition and the stereotypes about black women and brazilian “indian” women that were reiterated for so long. By breaking with it and occupying the social place of emancipation, these women also contribute to the shaping of a new social representation of the groups to which they belong.